Data clustering using min-min roughness and its application to cluster patients suspected diabetics - Mohd Ridzuan, Baharin (2012)
In the context of information technology nowadays,there are many data exists.All of this data are scrambled over inside the computer and with the presence of internet,even more data exist.The problem with this is,when we want the needed data only,there are too many to look for and they are all scrambled over the internet databases.Therefore,there are techniques that are proposed that will provide a way to automatically mine the data and obtain only meaningful data from the huge data over the internet.The area discussed in this research is Knowledge Discovery in Databases (KDD) and the technique used is Minimum-Minimum Roughness (MMR).The dataset used will be the dataset of diabetic patients.By using this MMR technique, I intended to cluster the diabetic dataset n which each cluster will contain the data most related to each other.